Evaluation of Naked Eye Single Tube Red Cell Osmotic Fragility Test (NESTROFT) in Screening and Diagnosis of Beta Thalassaemia Trait in Pakistani Population - Rubina Ghani; Nazish Jaffar; Abdul Rehman (ziauddin University, 2024)
Background: Beta thalassaemia, an inherited disease that is a cause of continuous burden on the affected families and the society. The objective of the study was to evaluate the efficacy of Naked Eye Single Tube Red Cell Osmotic Fragility Test (NESTROFT) for the detection of beta thalassaemia trait when used for the screening in Pakistani population. Methods: All participants requesting a complete blood count were included in the study. Informed consent was obtained. Naked Eye Single Tube Red Cell Osmotic Fragility Test was performed with freshly prepared 0.36% buffered saline. Turbidity in the tubes was an indication for individuals to be positive for beta thalassaemia trait. Hemoglobin electrophoresis was performed on all positive cases to confirm the sensitivity and the reliability of the screening test. Chi-Square test was used to test for any significant correlation between the different hematological parameters and other variables. Results: A total of 812 patients were included in the study from January 2017 to June 2017. The mean age of participants was 35.5 + 13.6 years. There were 351 (43.2%) male and 461 (56.7%) female participants. A 100% Naked Eye Single Tube Red Cell Osmotic Fragility Test sensitivity was obtained with 65 (8%) positive cases having HbA2 levels of more than 3.2% indicating their true positivity whereas, all 747 (92%) negative cases having HbA2 levels of less than 3.2% indicating their true negativity. Conclusion: NESTROFT was found a highly sensitive, cost-effective, and a rapid screening test for the identification of carriers of beta thalassaemia trait in our population. Keywords: Consanguineous Marriage; Population; Thalassaemia; Screening.